CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF CYSTIC ECHINOCOCCOSIS REGISTERED IN AN ENDEMIC AREA IN THE CENTRAL ANDES OF PERU (1991–2002)* - Salgado Díaz, Sara (2007)
Echinococcosis by Echinococcus granulosus is a problem of public health in Peru. The objective of the study was to describe the clinical and epidemiological characteristics of cystic echinococcosis cases diagnosed between 1991 and 2002 in the department of Junín in the central Andes of Peru. It was an observational study, historical cases series design. We reviewed the clinical records in hospitals of Junín to identify cases that concurred with the definition of probable and confirmed case. 1100 cases were identified, the average age ranging between 29.2 ± 18.3 years of age, 80.5% (886) confirmed. The disease is more common in women (p = 0,000022) and in who hadn’t completed elementary education (p= 0,001083). Out of all the series, the group of 5 to 19-year olds presented four hundred and three cases (36.7%). Five hundred and eighty one cases (52.8%) had a background of exposure to dogs and two hundred thirty cases (20.9%) had been exposed to other animals. In confirmed cases, hospital readmission was one hundred twenty six (14.2%). In four hundred and twelve cases (46.5%) its localisation was pulmonary; and hepatic in three hundred and thirty one cases (37.4%). The distribution by departments was 951 cases (86.5%) detected in Junín and 92 cases (8.4%) in Huancavelica; 438 cases (39.8%) were identified in the province of Huancayo (Junín) and 129 cases (11.7 %) in the district of El Tambo. Cystic echinococcosis in the department of Junín is a serious public health problem, significantly affecting more women and young people. Localisation is mainly pulmonary and the rate of hospital readmission is the highest in Latin America.